2007
DOI: 10.1128/jvi.00960-06
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between a 54-Kilodalton Mammalian Cell Surface Protein and Cowpea Mosaic Virus

Abstract: Cowpea mosaic virus (CPMV), a plant virus that is a member of the picornavirus superfamily, is increasingly being used for nanotechnology applications, including material science, vascular imaging, vaccine development, and targeted drug delivery. For these applications, it is critical to understand the in vivo interactions of CPMV within the mammalian system. Although the bioavailability of CPMV in the mouse has been demonstrated, the specific interactions between CPMV and mammalian cells need to be characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 68 publications
(62 reference statements)
1
66
0
Order By: Relevance
“…Phages and CPMV have evolved to bind and replicate in bacteria and plants respectively, therefore were anticipated to have different circulation half lives in mammalian systems. However, unlike phages, CPMV particles were found to bind to a 54 kDa protein expressed on a variety of mammalian cells including endothelial cells [25]. The rapid removal of CPMV from circulation may be related to this uptake of CPMV in endothelial cells [29].…”
Section: Discussionmentioning
confidence: 99%
“…Phages and CPMV have evolved to bind and replicate in bacteria and plants respectively, therefore were anticipated to have different circulation half lives in mammalian systems. However, unlike phages, CPMV particles were found to bind to a 54 kDa protein expressed on a variety of mammalian cells including endothelial cells [25]. The rapid removal of CPMV from circulation may be related to this uptake of CPMV in endothelial cells [29].…”
Section: Discussionmentioning
confidence: 99%
“…In the past two decades, taking advantages of distinctive chemical and biological properties of plant viruses, new materials with unique structural features have been developed for a wide range of applications, including electronics, drug delivery, imaging, gene therapy, and immunotherapy [35][36][37][38][39][40][41][42][43][44][45][46][47]. Recent studies have reported that cowpea mosaic virus (CPMV) can interact with the mammalian cells due to the presence of two highly specific CPMV-binding proteins present in certain mammalian cells [48]. Furthermore, it was found that the rigid, densely arranged, and ordered repetitive protein display of coat proteins of viral capsids results in the mature B cells recognition and induces the IgM response [49].…”
Section: Introductionmentioning
confidence: 99%
“…The agglomeration of iron oxide nanoparticles after incubated with cells that we observed in TEM images may also be caused by smaller surface charge after protein adsorption and the repulsive forces by negatively charged cell surface. The uptake mechanism of CPMV nanoparticle by human cells is little known, but a recent study of CPMV have identified a mediated endocytosis of CPMV via a 54 kD protein found on the plasma membrane of both human and muring cell lines (Koudelka et al 2007). Figure 6 reveals the changes of Zeta potential values with theoretical fittings for MCF10A normal cells and MCF7 cancer cells after incubated with iron oxide and CPMV nanopaticles.…”
Section: Theory and Analysismentioning
confidence: 99%
“…Cowpea mosaic virus (CPMV) is one of the smallest plant viruses, which is an icosahedron with a spherical average diameter of 28.4 nm that built from 60 copies of two asymmetric protein units assembled around a single-stranded bipartite RNA genome (Lewis et al 2006;Blum et al 2004). Its highly organized nanoblock structure, chemically addressable sites on the protein shell (the capsid) surface, and pH and thermally stability over a wide range of conditions make CPMV an excellent choice in biomedical applications including vaccines, vascular imaging, and targeted drug delivery (Lewis et al 2006;Koudelka et al 2007;Lomonossoff et al 1999). …”
Section: Introductionmentioning
confidence: 99%